TINJAUAN YURIDIS KEWENANGAN HAK ANGKET DEWAN PERWAKILAN RAKYAT TERHADAP KOMISI PEMBERANTASAN KORUPSI - Satriyo Amukti Wibowo (MIMBAR YUSTITIA, 2020)
The authority of the supervisory agency in writing this article, is focused on the authority of the DPR as a supervisory agency in overseeing the performance of other state institutions, by reviewing the 1945 Constitution, Law Number 17 of 2014 concerning MD3 (MPR, DPR, DPD, and DPRD), Law No. Number 30 of 2002 concerning the Corruption Eradication Commission (KPK), and the decision of the Constitutional Court (constitutional court) number 36/PUU-XV/2017. The research in this paper emphasizes the authority of the DPR in providing questionnaires to the KPK. The research method in this paper is a normative juridical approach with a statute approach, a conceptual approach, and a historical approach. The purpose of the research is simply to find out the provisions and regulations regarding the authority of the supervisory agency and to examine from a legal aspect the authority of the DPR as a supervisory agency in providing questionnaires to the KPK as an independent state institution. In carrying out their duties and authorities, they are independent and free from any power. The main results of the research can be concluded that the authority of the DPR as a state institution has three functions, namely, the legislative function, the budget function, and the supervisory function as stated in Article 20A paragraph (1) of the 1945 Constitution, and in carrying out these functions the DPR is also supported by several rights, namely, the right of interpellation, the right of inquiry, and the right to express an opinion, which are also stated in Article 20A paragraph (2) of the 1945 Constitution, but based on law number 30 of 2002 concerning the Corruption Eradication Commission (KPK), it is explained that the KPK is an institution independent country. The authority of the DPR as a supervisory agency in supervising state institutions, in this study the DPR gave a questionnaire to the KPK on a case that was considered important, strategic, and had a broad impact on the Indonesian people and nation.